Transformacja systemu informacyjnego małej firmy doradczej w ramach wdrożenia ISO 9001:2000 : Studium przypadku - Podemski, Wojciech (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The paper refers to a change of information system as a project in frames of implementation the quality management system, according to ISO 9001:2000 executed in small consulting company. The goal of the change is to improve operational efficiency of the company which determines achievement of business goals. This article is an attempt of systematic approach to significant change in small service company and presentation it as the general practice in this kind of enterprises. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 213-221